The Differential Effects of Heat Therapy, Ice Bath, and Massage on Central and Peripheral Fatigue and the Neuromuscular System: A Review (Development Engineering Conferences Center Articles Database, 2025)
This review focuses on optimizing athlete recovery during training and competition. While existing literature thoroughly explores recovery scenarios, additional insights are needed for practical application. Performance induces stress on the body, which can be harmful or beneficial based on individual responses. Key recovery methods include proper nutrition, rest, heat therapy, ice baths, and massage, each tailored to physiological needs. Factors like sex, age, and specific demands should guide recovery strategies, emphasizing individual requirements. While techniques like heat therapy and ice baths can enhance circulation and recovery, the placebo effect should be acknowledged. It’s essential to consult professionals for personalized recommendations. Peripheral fatigue (PF) is manageable, but central nervous system (CNS) exhaustion complicates recovery; consulting a practitioner is advisable to avoid performance degradation issues.